Ecopedagogy Based Curriculum Innovation to Foster Environmental Sustainability Awareness among Indonesian Generation Z - Emha Dzia`Ul Haq; Muhammad Rizal Masdul; Oktafiani Larasati (Institut Bahri Asyiq Galis Bangkalan, 2025)
Global and national environmental crises have demanded a strategic role of education in fostering sustainability awareness among younger generations, particularly Generation Z in Indonesia. The formal education curriculum has not fully succeeded in cultivating critical and sustainable ecological awareness, as it has remained predominantly oriented toward cognitive mastery and fragmented content delivery. This study aimed to comprehensively analyze the role of ecopedagogy-based curriculum innovation in promoting environmental sustainability awareness among Indonesian Generation Z. The research employed a qualitative descriptive approach using a Systematic Literature Review design of scholarly articles and academic publications published between 2018 and 2025 and indexed in the Scopus, Google Scholar, and SINTA databases. Data were analyzed through thematic analysis to synthesize patterns, trends, and key findings across studies. The findings indicated that an ecopedagogy-based curriculum effectively enhanced sustainability awareness through the integration of ecological values, critical-reflective pedagogy, and action-oriented as well as digitally contextualized learning aligned with the characteristics of Generation Z. This study contributed theoretically by strengthening the conceptual framework of ecopedagogy in curriculum innovation and offered practical implications for policy development and sustainable education practices in Indonesia.